Breaking the cycle of emotional flooding: the protective role of women’s emotional intelligence in couple’s conflict - Berenguer-Soler, María; García del Castillo-López, Álvaro; Pineda, David (Frontiers in Psychology, 2023)
One of the most damaging aspects, both for people's well-being and for close relationships, is conflict. Beyond different stressors, the emotions evoked, their regulation and an appropriate conflict resolution strategy will reduce negative consequences. Emotional Intelligence facilitates social relationships, but little applied research has been done on the relationship with couple conflict and emotional flooding, particularly from the perspective of women. Therefore, the present study analyses the role of Perceived Emotional Intelligence (PEI) and the mediating effect of Positive Conflict Resolution strategies (PCR) in couples' conflicts from women's perspective, examining its effect on Emotional Flooding (EF) and Satisfaction. Methods: Through a cross-sectional design, the relationships between variables were analysed using group comparisons and means of a structural equation model (SEM) in a sample of 692 women. Results: Significant differences were found between the groups by age, length of relationship, and motherhood. The SEM revealed a good fit. PEI predicted 71.8% of the variance in EF and 35% in Satisfaction through PCR and Conflict.